A Governing Framework for Climate Change Adaptation in the Built Environment - Daniel A. Mazmanian; John Jurewitz; Hal T. Nelson (Ecology and Society, 2013)
Developing an approach to governing adaptation to climate change is severely hampered by the dictatorship of the present when the needs of future generations are inadequately represented in current policy making. We posit this problem as a function of the attributes of adaptation policy making, including deep uncertainty and nonstationarity, where past observations are not reliable predictors of future outcomes. Our research links organizational decision-making attributes with adaptation decision making and identifies cases in which adaptation actions cause spillovers, free riding, and distributional impacts. We develop a governing framework for adaptation that we believe will enable policy, planning, and major long-term development decisions to be made appropriately at all levels of government in the face of the deep uncertainty and nonstationarity caused by climate change. Our framework requires that approval of projects with an expected life span of 30 years or more in the built environment include minimum building standards that integrate forecasted climate change impacts from the Intergovernmental Panel on Climate Change (IPCC) intermediate scenario. The intermediate IPCC scenario must be downscaled to include local or regional temperature, water availability, sea level rise, susceptibility to forest fires, and human habitation impacts to minimize climate-change risks to the built environment. The minimum standard is systematically updated every six years to facilitate learning by formal and informal organizations. As a minimum standard, the governance framework allows jurisdictions to take stronger actions to increase their climate resilience and thus maintain system flexibility.